Establishing Parenting Time in Child Support Cases: New Opportunities and Challenges1. (April 2015) - Pearson, Jessica
<x xml:space="preserve">Abstract</x> Despite dramatic increases in collections, child support frequently fails to be the linchpin to family self‐sufficiency that it could be, and many researchers, advocates and policymakers have concluded that future progress in collections will require making the child support system more fair and responsive to its growing poor, never‐married caseload. High on the list of suggested reforms is paying more attention to involving poor fathers in the lives of their children. Since the inception of the child support program in 1975, parenting time and child support have been legally distinct issues and activities pertaining to parenting time have not qualified for the 66 percent of funding that the federal government provides to fund the child support program. As a result, few child support programs address parenting time when they establish or enforce child support orders. Public Law 113–183 (2014) includes a provision to encourage the establishment of safe parenting time arrangements in new child support orders, although the activity is voluntary and no new funding is provided. This article describes the treatment of parenting time in the child support program and the approaches that some states and local jurisdictions have adopted to develop and incorporate parenting time responsibilities with family violence safeguards in new child support orders. This includes the use of standard parenting time schedules, self‐help resources, mediation or facilitation with a neutral third party, and comprehensive programs that attempt to address multiple barriers. Key Points for the Family Court Community Parenting time and child support are legally distinct issues and courts typically order child support for parents of children born out‐of‐wedlock without simultaneously ordering parenting time arrangements. Research shows that addressing parenting time improves parent‐child contact and child support payments and that positive paternal engagement improves child outcomes. A few state and local child support agencies address parenting time using standard parenting time schedules, self‐help resources for parents, mediation or facilitation with a neutral third‐party; and comprehensive programs that address multiple barriers. Developing a safe, structured approach to parenting time for the child support population will require coordination among courts, domestic violence programs and child support agencies, and allowing these activities to qualify for federal matching funds.